Constitutional Violations in the Operation and Use of Artificial Intelligence Systems - Zahrastnik, Kristjan (Od algoritma do prava: Pravni, ekonomski in kulturni izzivi umetne inteligence, 2025)
The chapter examines and critically analyses the operation and use of artificial intelligence systems from the perspective of constitutional law violations. Interferences with constitutionally protected rights arising from the operation and application of artificial intelligence systems occur on two levels: during their development and training, as well as in their use by end-users. The author focuses on intellectual property rights (copyright), protection of personal data, equality before the law (prohibition of discrimination), freedom of work (right to work), freedom of expression, right to personal dignity and safety, and protection of the rights to privacy and personality rights. In this context, the author also discusses relevant EU legal acts, such as the Artificial Intelligence Act, Directive (EU) 2019/790 on Copyright and Related Rights in the Digital Single Market, and the Digital Services Act.